Forgiveness pada penyintas perundungan: Bagaimana peranan dukungan sosial dan self-compassion? - Kuswoyo, Citra Ayu Damayanti; Dyan Evita Santi; Rahma Kusumandari (INNER: Journal of Psychological Research, 2023)
Abstract This study was to find the relationship between social support and self-compassion with forgiveness in early adulthood as survivors of bullying. This research is quantitative using correlational methods. There were 126 participants who were victims of bullying during elementary/middle/high school ages 19-25 years. The data analysis technique uses a Bayesian. This study used measurement tools with the scale of forgiveness, scale of social support, and scale of self-compassion. The results of the variable social support with forgiveness with a significant value of BF10 0.005 (BF10 <1.00), so that social support cannot be a significant predictor of forgiveness. In the variable Self-Compassion with Forgiveness with a significant value BF10 1.00 (BF10 = 1.00). Meaning that the higher the Self-Compassion, the higher the Forgiveness. For the variables of social support and self-compassion with forgiveness with a significant value BF10 0.231 (BF10 <1.00) social support and forgiveness simultaneously can’t be a significant predictor for forgiveness. Keywords: Bullying; Forgiveness; Self-Compassion; Social Support.